PENGARUH PEMBERIAN EDUKASI TENTANG TRIPLE ELIMINASI TERHADAP PENGETAHUAN DAN SIKAP IBU HAMIL DI PUSKESMAS PASAR USANG - Suganda, Yohana; Silvia, Elwitri; Rita Aninora, Novia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The achievement of triple elimination in Padang Pariaman Regency in 2021 is for HIV 67.97%, Syphilis 73.70% and Hepatitis B 68.83%. Whereas in 2022, the triple elimination achievement in Padang Pariaman Regency is for HIV 74.99%, Syphilis 74.99% and Hepatitis B 74.99%. The achievement of triple elimination at the Pasar Usang Health Center has met the target, namely for HIV 93.04%, Syphilis 93.04% and Hepatitis B 93.04%. The influencing factor is the provision of education to increase knowledge and attitudes. The aim of this study was to determine the effect of providing education about the elimination of threefold on the knowledge and attitudes of pregnant women at Pasar Usang Health Center. The research method is semi-experimental. The independent variable is education about triple elimination, while the dependent variable is knowledge and attitude of pregnant women. The population is pregnant women in the pregnant women class which was held in March 2023, with a total of 63 pregnant women. The sampling technique is accidental sampling. The instrument used is a questionnaire. The analysis in this study was univariate and bivariate analysis using the T-test statistic. The results of the study showed that there was a significant increase between the average value of knowledge before and the average value of knowledge after triple elimination education. There is a significant increase between the average value of the attitude before the average value of the attitude after the triple elimination education. In conclusion, there is an effect of education using leaflet media on increasing the knowledge and attitudes of pregnant women. It is recommended that the results of this study be used as input in making policies related to the implementation of the maternal health program in order to increase the coverage of triple elimination.Keywords: triple Eliminasi, Pengetahuan, Sikap